BURNOUT SEBAGAI IMPLIKASI KONFLIK PERAN GANDA (PEKERJAAN-KULIAH) PADA MAHASISWA YANG BEKERJA DI KOTA MAKASSAR - Syarief Dienan Yahya; Harry Yulianto (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2018)
This research is devoted to investigate role conflict form the context of work and university domains on working students. This research it is expected to fill research gaps and enrich studies of role conflict topic and its relation to stress and burnout. This study involved 239 active working students from various universities in Makassar as respondents. Determination of the sample was done randomly through a purposive sampling approach. The Statistical Package for the Social Sciences (SPSS) is used in assisting research data analysis includes path analysis and Moderated Regression Analysis. The results showed that the university -work conflict variables and work- university conflict variables had a significant positive effect on stress variables, while the university-work conflict variable had a insignificant negative effect on burnout and work- university conflict variables had a significant positive effect on burnout. Through Moderated Regression Analysis shows that social support variables reduce the negative influence of stress on burnout of Working Student.